2016
DOI: 10.1161/jaha.115.002485
|View full text |Cite
|
Sign up to set email alerts
|

HECT‐Type Ubiquitin E3 Ligase ITCH Interacts With Thioredoxin‐Interacting Protein and Ameliorates Reactive Oxygen Species–Induced Cardiotoxicity

Abstract: BackgroundThe homologous to the E6‐AP carboxyl terminus (HECT)–type ubiquitin E3 ligase ITCH is an enzyme that plays a pivotal role in posttranslational modification by ubiquitin proteasomal protein degradation. Thioredoxin‐interacting protein (TXNIP) is a negative regulator of the thioredoxin system and an endogenous reactive oxygen species scavenger. In the present study, we focused on the functional role of ubiquitin E3 ligase ITCH and its interaction with TXNIP to elucidate the mechanism of cardiotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Isolation and culture of neonatal rat cardiomyocytes (NRCMs) were performed as we previously described [21]. Briefly, ventricles were obtained from 1-to 2-day-old Sprague-Dawley rat pups (mixed gender) after euthanasia by decapitation, and cardiomyocytes were isolated by digestion with collagenase.…”
Section: Neonatal Rat Cardiomyocyte Isolation Cell Culture and Treamentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation and culture of neonatal rat cardiomyocytes (NRCMs) were performed as we previously described [21]. Briefly, ventricles were obtained from 1-to 2-day-old Sprague-Dawley rat pups (mixed gender) after euthanasia by decapitation, and cardiomyocytes were isolated by digestion with collagenase.…”
Section: Neonatal Rat Cardiomyocyte Isolation Cell Culture and Treamentioning
confidence: 99%
“…The total protein extracts were prepared with radio-immunoprecipitation assay (RIPA) buffer as we previously reported [21]. Equal amounts of protein were subjected to 10% SDS-PAGE and transferred to polyvinylidene difluoride membranes.…”
Section: Western Blottingmentioning
confidence: 99%
“…ITCH increases proteasomal TXNIP degradation and augments thioredoxin activity, leading to inhibition of ROS generation, p38 MAPK, and p53, improvement of oxidative stress response in ROS-induced cardiotoxicity, and improvement of survival in ROSinduced cardiotoxicity and myocardial infarction. [96] WWP1 also belongs to the E3 ubiquitinated ligase HECT family. It has been reported that WWP1 can degrade p53 through the ubiquitin-proteasome pathway.…”
Section: Journal Of Translational Internal Medicine / Apr-jun 2020 / mentioning
confidence: 99%
“…Moreover, iTcH plays an important role in regulating apoptosis and other biological processes (19). it has also been shown that in myocardial cells, Txnip is a target protein of ubiquitin molecules (20). By interacting with e3 ligase-iTcH, Txnip protein expression is degraded by ubiquitin, thus reversing the degree of myocardial cell apoptosis caused by myocardial infarction (20).…”
Section: Introductionmentioning
confidence: 99%